The role of salt ions and organic molecules in the self-assembled nanolayering. Issue 1 (2nd January 2021) - Zhang, Ling; Jin, Xinyang; Xu, Yuedan; Wang, Chaoyang; Li, Mingxing; Fu, Baiping
Abstract: This study investigated effects of polyacrylic acid (PAA) on nanolayering self-assembly, and effects of salt ions on the formation of nanolayering after their chemical interaction with 10-methacryloyloxydecyl dihydrogen phosphate (MDP). ACP–MDP suspension was prepared by dispersing 0.01 g ACP nanoparticles in 4 mL of a 5 wt% MDP solution. Then a PAA solution (100 or 500 μg/mL) was mixed into ACP–MDP suspension. The reaction products were analyzed by transmission electron microscope (TEM). After one of the following metal chlorides (each 0.076 mM of CaCl2, BaCl2, AlCl3, FeCl2, FeCl3, MnCl2, CuCl2, ZnCl2, or MgCl2 ) was dispersed in a 4 mL MDP solution, they were further analyzed by X-ray diffraction (XRD) and TEM. ACP nanoparticles in the MDP solution could self-assemble into ACP–MDP nanolayering composites. The TEM images show that an amount of ACP nanoparticles were aggregated and fused together after the addition of PAA into ACP–MDP suspensions, while no nanolayering was found. The XRD data and TEM images reveal that nanolayering was self-assembled after the chemical interaction of MDP with some metal chlorides (CaCl2, BaCl2, AlCl3, FeCl2, FeCl3, MnCl2 ), but not with the others (ZnCl2, CuCl2, MgCl2 ). PAA could inhibit the self-assembly of nanolayering. Some salt ions play an important role in highly ordered, self-assembled nanostructure after their chemical interaction with MDP. The finding is helpful for functional materials fabrication.